Effects of pentoxifylline in the treatment of abdominal sepsis in rats - Azevedo, Ítalo Medeiros; Pinheiro, Laíza Araújo Araújo Mohana; Torres, Cristhiane Araújo; Silva, Mayara Mytzi Aquino; Maciel Grossi, Thiago Roberto; Araújo-Filho, Irami; Rêgo, Amália Cinthia Meneses; Medeiros, Vítor Brasil; Carvalho, Marília Daniela Ferreira; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2010)
Objective: To evaluate the effects of pentoxifylline in the treatment of abdominal sepsis in rats submitted to cecal ligation and puncture (CLP). Methods: We used 18 Wistar male rats three months old, randomly divided into control group C (n = 6); CLP (n = 6) for the rats submitted to CLP; Group CLP + PTX (n = 6) whose rats were treated with pentoxifylline and submitted to CLP. Pentoxifylline (40mg/Kg) was injected intraperitoneal 2 hours before and 8 hours after the induction of peritonitis. Histopathology of the lung, liver and kidney as well as analysis of renal function, markers of liver injury and cytokines were studied. The results were compared through ANOVA, and post hoc by Bonferroni test, considering p <0.05 as significant. Results: The control group rats showed lower levels of all cytokines, compared to CLP group (p <0.05). The CLP+PTX rats showed significantly lower amounts of TNF-? and IL-1 ? when compared to the CLP group, but similar to group C. The levels of IL-6 in Group CLP+PTX, were higher than that found in group C and lower than that found in Group CLP (p <0.05). Reduction of urea and creatinine occurred after administration of pentoxifylline. The values of AST and ALT were slightly lower in the experimental group, and no significant difference was observed comparing with the control group. The microscopic findings of kidney, liver and lung revealed less inflammatory reaction associated with the reduction of pathological changes in animals treated with pentoxifylline. Conclusion: The pentoxifylline attenuated the pathophysiological events of sepsis, reducing the expression of pro-inflammatory cytokines, preserving renal function and tissue injury in an experimental model of polymicrobial sepsis.